Microstructure and optical properties of ? - Fe2 O3 containing F-centres - Stashans, A. (2010)
Effects produced in the hematite (?-Fe2O3) crystal due to the presence of F-centre are reported in the present work. The results are based on the performed quantum-chemical modelling using the Hartree-Fock methodology. A supercell consisting of 120 atoms has been used throughout the computations. First, the required numerical parameters for the Fe atom are obtained by reproducing fairly well the main features of a pure material. Then, the neutral F-centre defect has been introduced and its influence upon the microstructure and electronic properties in the hematite is determined. The acquired atomic shifts around the F-centre imply the significance of the Coulomb interaction in this material. However, the defect-induced electron density redistribution has to be taken into consideration in order to explain explicitly the atomic relaxation. Presence of the F-centre induces a local energy level in gap between the upper valence band and the conduction band, which imparts to the absorption spectra of the material with two values, 0.9 eV and 3.6 eV. © 2009 Elsevier Ltd. All rights reserved.